2018
DOI: 10.4088/jcp.17m11958
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Prescription Medication Misuse Among Young Adults in the United States

Abstract: Objectives This study examined prescription drug misuse (PDM), sources of PDM and substance use disorder (SUD) symptoms as a function of educational status among U.S. young adults based on a large nationally representative sample. Methods Data from the 2009–2014 National Survey on Drug Use and Health came from a sample of 106,845 young adults aged 18–25 years. Respondents were categorized by educational status and PDM, sources of PDM, other substance use, and SUD symptoms, with analyses performed separately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
71
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 31 publications
4
71
1
Order By: Relevance
“…Fewer studies report on the behaviors surrounding the acquisition and administration of stimulants among students who misuse prescription stimulants and whether these behaviors differ among different subtypes of those who endorse NMUPS. In consensus with others, 6,18 McCabe et al recently reported that among college students who use prescription stimulants nonmedically, 37% received stimulants at no cost from a friend or relative 19 and that most used others' prescriptions 20 . Furthermore, most studies have found that oral administration was the most common route of administration with a minority of students using stimulants intranasally 5,18,21,22 .…”
Section: Introductionmentioning
confidence: 93%
“…Fewer studies report on the behaviors surrounding the acquisition and administration of stimulants among students who misuse prescription stimulants and whether these behaviors differ among different subtypes of those who endorse NMUPS. In consensus with others, 6,18 McCabe et al recently reported that among college students who use prescription stimulants nonmedically, 37% received stimulants at no cost from a friend or relative 19 and that most used others' prescriptions 20 . Furthermore, most studies have found that oral administration was the most common route of administration with a minority of students using stimulants intranasally 5,18,21,22 .…”
Section: Introductionmentioning
confidence: 93%
“…Secondary school dropout is associated with negative health, social, and economic outcomes (Amos, 2009;Russell, 2011). Youth who do not complete secondary school are at increased risk for unhealthy substance use (Maynard, Salas-Wright, & Vaughn, 2015;McCabe, Teter, Boyd, Wilens, & Schepis, 2018;Reingle Gonzalez et al, 2016).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Secondary school dropout is associated with negative health, social, and economic outcomes (Amos, ; Russell, ). Youth who do not complete secondary school are at increased risk for unhealthy substance use (Maynard, Salas‐Wright, & Vaughn, ; McCabe, Teter, Boyd, Wilens, & Schepis, ; Reingle Gonzalez et al, ). In addition, youth who drop out of secondary school prior to graduation have the highest prevalence of opioid misuse compared to other youth (McCabe et al, ; Schepis, Teter, Mccabe, ).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Pressure from the academic environment, perceived peer approval and behavior, also the large and diverse social networks of college students may contribute to opioid misuse. 1,[7][8][9][10] Although students have reported misusing opioids for the treatment of emotional pain, it appears that motivation for misuse is largely recreational. 2,6,11 Characteristics specific to college students place them not only at risk for substance use but also to mental health complications, particularly depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%